Chronic Hyperinsulinaemic Hypoglycaemia in Rats Is Accompanied by Increased Body Weight, Hyperleptinaemia, and Decreased Neuronal Glucose Transporter Levels in the Brain - Vivi F. H. Jensen; Anne-Marie Mølck; Melissa Chapman; Lene Alifrangis; Lene Andersen; Jens Lykkesfeldt; Ingrid B. Bøgh (International Journal of Endocrinology, 2017)
The brain is vulnerable to hypoglycaemia due to a continuous need of energy substrates to meet its high metabolic demands. Studies have shown that severe acute insulin-induced hypoglycaemia results in oxidative stress in the rat brain, when neuroglycopenia cannot be evaded despite increased levels of cerebral glucose transporters. Compensatory measures in the brain during chronic insulin-induced hypoglycaemia are less well understood. The present study investigated how the brain of nondiabetic rats copes with chronic insulin-induced hypoglycaemia for up to eight weeks. Brain level of different substrate transporters and redox homeostasis was evaluated. Hyperinsulinaemia for 8 weeks consistently lowered blood glucose levels by 30–50% (4–6 mM versus 7–9 mM in controls). The animals had increased food consumption, body weights, and hyperleptinaemia. During infusion, protein levels of the brain neuronal glucose transporter were decreased, whereas levels of lipid peroxidation products were unchanged. Discontinued infusion was followed by transient systemic hyperglycaemia and decreased food consumption and body weight. After 4 weeks, plasma levels of lipid peroxidation products were increased, possibly as a consequence of hyperglycaemia-induced oxidative stress. The present data suggests that chronic moderate hyperinsulinaemic hypoglycaemia causes increased body weight and hyperleptinaemia. This is accompanied by decreased neuronal glucose transporter levels, which may be leptin-induced.